2020
DOI: 10.1186/s12883-020-01648-w
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells participate in the recovery of ischemic stroke patients

Abstract: Background: Recent preclinical studies have shown that regulatory T cells (Treg) play a key role in the immune response after ischemic stroke (IS). However, the role of Treg in human acute IS has been poorly investigated. Our aim was to study the relationship between circulating Treg and outcome in human IS patients. Methods: A total of 204 IS patients and 22 control subjects were recruited. The main study variable was good functional outcome at 3 months (modified Rankin scale ≤2) considering infarct volume, E… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 54 publications
0
16
0
2
Order By: Relevance
“…Co-culturing astrocytes with splenic T cells showed that astrocytes help to sustain FOXP3 expression in Tregs through IL-2/STAT5 signaling ( 114 ). Recently, a study reported higher circulating Tregs and serum IL-10 level at 48 and 72 hours after stroke onset in patients ( 115 ). To further identify the association of Tregs frequency with clinical outcomes, stroke patients are divided into two groups based on disease outcome (good vs. poor based on modified Rankin scale) and found the poor clinical outcomes with a higher infection risk especially in patients with lower Tregs frequency at 48 hours after stroke ( 115 ).…”
Section: Tregs Interact With Central Nervous System-resident Cellsmentioning
confidence: 99%
“…Co-culturing astrocytes with splenic T cells showed that astrocytes help to sustain FOXP3 expression in Tregs through IL-2/STAT5 signaling ( 114 ). Recently, a study reported higher circulating Tregs and serum IL-10 level at 48 and 72 hours after stroke onset in patients ( 115 ). To further identify the association of Tregs frequency with clinical outcomes, stroke patients are divided into two groups based on disease outcome (good vs. poor based on modified Rankin scale) and found the poor clinical outcomes with a higher infection risk especially in patients with lower Tregs frequency at 48 hours after stroke ( 115 ).…”
Section: Tregs Interact With Central Nervous System-resident Cellsmentioning
confidence: 99%
“…Studies conducted on cardiovascular diseases, e.g., atherosclerosis, hypertension, acute coronary syndrome, and stroke, have indicated that immunosuppressive cells were involved in the pathology of CVD [ 116 119 ]. For instance, the occurrence of a stroke increased the level of Tregs which attenuated inflammatory responses and enhanced the appearance of post-stroke regeneration [ 119 , 120 ]. Accordingly, stroke increased the level of circulating M-MDSCs in human stroke patients [ 121 ].…”
Section: Clinical Interactions Between Aging and Chronic Inflammatory...mentioning
confidence: 99%
“…Th1 cells secrete proinflammatory cytokines and Th2 cells produce anti-inflammatory cytokines ( 87 ). It is important to note that Treg cells, which are identified by expression of transcription factor forkhead box (FOX)P3, play a beneficial role in stroke ( 88 , 89 ). Treg cells are rare in the early stages of the disease.…”
Section: The Bridgehead: Neuroinflammationmentioning
confidence: 99%
“…Promotion and maintenance of the anti-inflammatory phenotype of microglia is another important mechanism by which Treg cells play a neuroprotective role ( 92 ). Hence, Treg cells could be an effective target for the treatment of stroke in the future ( 89 ).…”
Section: The Bridgehead: Neuroinflammationmentioning
confidence: 99%